Human poisoning in Thailand: The Ramathibodi Poison Center's experience (2001-2004) - Winai Wananukul (2018)
Objective. To identify poisoning and toxic exposure pattern, severity, and clinical outcome in Thailand during 2001 to 2004. Method. This is a prospective study. All inquiries were registered, followed up, and verified. Interlocutors, poisons, patients' profiles, severity, and medical outcome after exposure or poisoning were analyzed. Results. A total 14,428 events was suspected as human poisoning or exposure. After follow-up and verification, 98.9% were confirmed as poisoning or poison exposure. These involved 15,016 patients and accounted for 6.0 per 100,000 populations per year. The vast majority of calls (92.4%) were from physicians. Pesticides, household products, and pharmaceutical products were the most common poisons involved in human exposure, which were 41.5%, 19.5%, and 18.9%, respectively. Patients aged 0-6 years, teenagers and adults with 20-29 years of age had the highest rates of exposure, which were 33.0, 24.5, and 10.5 exposures per 100,000 per year, respectively. Unintentional accidental exposure is the major reason of exposure in children, but intentional suicide was the main reason of exposure in teenagers and adults. The death rate of all exposure was 5.5%. Pesticides cause more severe clinical course and the highest death rate (10.0%). Conclusion. Features of poisoning in Thailand were different from those in Western countries. Pesticide poisoning was the major problem in Thailand. Intentional suicide was the major circumstance of poison exposure in adults, but accidental exposure was the major reason of exposure in children. Copyright © Informa Healthcare.